Measuring and structuring the spatial coherence length of organic light‐emitting diodes. Issue 1 (26th November 2015) - Xie, Guohua; Chen, Mingzhou; Mazilu, Michael; Zhang, Shuyu; Bansal, A.K.; Dholakia, Kishan; Samuel, Ifor D. W.
Abstract : The spatial coherence length of light beams from organic light‐emitting diodes (OLEDs) is an important feature of their light emission that has been barely studied. A method and optical setup for measuring spatial coherence length using Young's double‐slit experiment is reported and applied to a range of OLEDs with different emitters and device architectures. The spatial coherence lengths of planar OLEDs are approaching 2 μm and can be enhanced by integrating external diffractive optical elements. Abstract: The spatial coherence of organic light‐emitting diodes (OLEDs) is an important parameter that has gained little attention to date. Here, we present a method for making quantitative measurements of the spatial coherence of OLEDs using a Young's double‐slit experiment. The usefulness of the method is demonstrated by making measurements on a range of OLEDs with different emitters (iridium and europium complexes) and architectures (bottom and top emitting) and the fringe visibility is further manipulated by gratings embedded in external diffractive optical elements. Based on the experiments and simulation of the results, we quantitatively determine the spatial coherence lengths of several OLEDs and find them to be a few micrometers. A 60% increase in the spatial coherence length was observed when using a narrow bandwidth emitter and a metal‐coated grating.